2010
DOI: 10.1007/bf03262716
|View full text |Cite
|
Sign up to set email alerts
|

Best Clinical Practice Guidance for clinicians dealing with children presenting with Molar-Incisor-Hypomineralisation (MIH)

Abstract: MIH is an important clinical problem that often concerns both the general dental and specialist paediatric dentists; the present 'best clinical practice guidance' aims to further help clinicians dealing with the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
450
1
109

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 401 publications
(575 citation statements)
references
References 18 publications
15
450
1
109
Order By: Relevance
“…4,5 Since the early mineralization phase of the FPMs occurs close to birth until the first year of life, the teeth are susceptible to the various etiological factors causing MIH during this critical stage of tooth development. 8 Lygidakis et al 5 found that MIH was more common in a study group with perinatal complications of Caesarean section, premature birth, prolonged delivery and twinning. This case report presented monozygotic twins that were born on term, via Caesarean section delivery with a normal birth weight.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…4,5 Since the early mineralization phase of the FPMs occurs close to birth until the first year of life, the teeth are susceptible to the various etiological factors causing MIH during this critical stage of tooth development. 8 Lygidakis et al 5 found that MIH was more common in a study group with perinatal complications of Caesarean section, premature birth, prolonged delivery and twinning. This case report presented monozygotic twins that were born on term, via Caesarean section delivery with a normal birth weight.…”
Section: Discussionmentioning
confidence: 97%
“…8,14 Weerheijm et al 15 also proposed that the clinical appearance of the 4 FPMs and 8 incisors should be recorded for the following features which will aid in the correct diagnosis of the condition: presence or absence of demarcated opacities; post eruptive enamel breakdown; atypical restorations; extraction of a FPM; failure of eruption of a FPM or an incisor. Teeth affected by MIH, with or without enamel loss, are often associated with hypersensitivity to air and cold stimuli.…”
Section: Case Reportsmentioning
confidence: 99%
See 3 more Smart Citations